Analysis of and prognostic information from disseminated tumour cells in bone marrow in primary breast cancer: a prospective observational study - Falck Anna-Karin; Bendahl Pär-Ola; Ingvar Christian; Isola Jorma; Jönsson Per-Ebbe; Lindblom Pia; Lövgren Kristina; Rennstam Karin; Fernö Mårten; Rydén Lisa (BMC Cancer, 2012)
Abstract Background Disseminated tumour cells (DTCs) in the bone marrow of patients with breast cancer have been identified as an independent predictor of poor prognosis in patients with non-metastatic disease. This prospective study aimed to evaluate the presence and prognostic value of DTCs in the bone marrow of female patients with primary breast cancer. Methods Between 1999 and 2003, bone marrow aspirates were obtained from patients at the time of surgery for primary invasive breast cancer. DTCs in bone marrow were identified using monoclonal antibodies against cytokeratins for detection of epithelial cells. The detection of DTCs was related to clinical follow-up with distant disease-free survival (DDFS) and breast cancer-specific survival as endpoints. Bone marrow aspirates from adult healthy bone marrow donors were analysed separately. Results DTCs were analysed in 401 patients, and cytokeratin-positive cells were found in 152 of these (38%). An immunofluorescence (IF) staining procedure was used in 327 patients, and immunocytochemistry (IC) was performed in 74 patients. The IF-based method resulted in 40% DTC-positive cases, whereas 30% were positive using IC (p = 0.11). The presence of DTCs in bone marrow was not significantly related to patient or tumour characteristics. The presence of DTCs was not a prognostic factor for DDFS (IF: hazards ratio [HR], 2.2; 95% confidence interval [CI], 0.63–2.2; p = 0.60; IC: HR, 0.84; 95% CI, 0.09–8.1; p = 0.88). Significant prognostic factors were lymph node metastases, oestrogen receptor positivity, Nottingham histological grade, and tumour size using Cox univariate analysis. The analyses were positive for epithelial cells in bone marrow from adult healthy donors in 19 (25%) samples. Conclusions The detection of DTCs in bone marrow in primary breast cancer was previously shown to be a predictor of poor prognosis. We were not able to confirm these results in a prospective cohort including unselected patients before the standard procedure was established. Future studies with a standardised patient protocol and improved technique for isolating and detecting DTCs may reveal the clinical applications of DTC detection in patients with micrometastases in the bone marrow.